PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL DISCOVERY LEARNING DI KELAS IV SDN 29 BATANG ANAI KABUPATEN PADANG PARIAMAN - Dinny Salfiyah Utami; Atri Waldi; Reinita; Tin Indrawati (EDU RESEARCH, 2024)
The aim of this research is to describe the improvement in learning outcomes of Pancasila education using the Discovery Learning model in class IV of SD Negeri 29 Batang Anai, Padang Pariaman Regency. This research is Classroom Action Research (PTK) which uses qualitative and quantitative approaches. Implemented in two cycles. and each cycle has four stages, namely planning, implementation, observation, and reflection. The research subjects were teachers and students of class IV SD Negeri 29 Batang Anai, Padang Pariaman Regency, totaling 20 students. The results of the research show an increase in: a) teaching modules in cycle I with an average of 79.16% (C), and cycle II 94.44% (A), b) implementation in the teacher aspect of cycle I with an average of 82.81 % (B), and cycle II 93.75% (A), while in the student aspect of cycle 1 with an average of 79.68 (C), and cycle II 90.62% (A), c) assessment of Students in cycle I obtained an average of 78.94 and cycle II with an average of 83.14. Based on these results, it can be concluded that using the Discovery Learning model can improve student learning outcomes in class IV Pancasila education learning at SD Negeri 29 Batang Anai, Padang Pariaman Regency.